Determination of Serum Inhibin-A Levels in Differentiating Pre-Eclampsia and Gestational Hypertension - Shah, Shahrukh; Aamir, Muhammad; Haroon, Zujaja Hina; Bibi, Afshan; Akber, Rabiya; Khalid, Usama Bin (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the association of serum Inhibin-A levels in differentiating Pre-eclampsia and gestational hypertension.Study Design: Cross-sectional study.Place and Duration of Study: Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology (AFIP) Rawalpindi, in collaboration with the Gynaecology and Obstetrics Department at Combined Military Hospital (CMH), Rawalpindi Pakistan, from Jul 2020 to Jun 2021.Methodology: Nulliparous women with single pregnancy in the third trimester admitted to evaluate high blood pressure in the Department of Gynaecology and obstetrics CMH Rawalpindi were selected after getting their informed written consent. Forty women with pre-eclampsia, forty with gestational hypertension, and 40 normotensive pregnant healthy women receiving routine antenatal care were matched for parity, age, and gestational age.Results: The concentration of inhibin A [Median (IQR)] in women having preeclampsia were significantly higher [1745 pg/ ml (1601.2–1821.7)] than subjects with gestational hypertension [895 pg/ml (834.5-977.5)] and normotensive pregnant women [637pg/ml (589-684.7)] with p-value 0.001. Further, Women with severe preeclampsia had a considerably greater serum concentration of inhibin A [Median (IQR)] [1895 pg/ml (1827.2-1955.7)] than those with mild preeclampsia [1686 pg/ml (1537.5-1762.7)].Conclusion: As per our study, median serum Inhibin A concentrations were higher in pre-eclampsia subjects than in gestational hypertension. In clinical situations, serum Inhibin A levels may be used to differentiate between pre-eclampsia and gestational hypertension.